Action Under the Labor Arbitration Acts - Cummings, Edward (Quarterly Journal of Economics, 1887)
Journal Article Action under the Labor Arbitration Acts Get access Edward Cummings Edward Cummings Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 4, July 1887, Pages 487–497, https://doi.org/10.2307/1879344 Published: 01 July 1887